Reason and Faith in Meister Eckhart: An Historical Approach - McGinn, Bernard (Laval théologique et philosophique)

(untitled) (Faculté de philosophie, Université Laval, 2025)
Eckhart’s view of the relation of reason and faith is known for eliding the careful line between the two ways of knowing God set out by Thomas Aquinas. This is true, but needs to be qualified. First, Eckhart insisted there was a difference in the certainty of the teaching of revelation and of human knowing. Second, the theologian could make use of forms of knowing accessible to reason, as well as forms dependent on divine light raising the mind to truths ordinarily beyond it (cognitio per speculum et in lumine). Third, knowing divine truths is located in intellectus/vernünfticheit, a dimension of the soul beyond mere reason.